Implementasi Algoritma Floyd Warshall pada Pencarian Lokasi Puskesmas di Kabupaten Karanganyar - Tristanto, Bayu; Hasbi, Muhammad; Vulandari, Retno Tri; Widada, Bebas; Kusumaningrum, Andriani (Jurnal Ilmiah SINUS, 2024)
One of the key public health service facilities is Public Health Center (Puskesmas). For new residents, it is very important to have information about the location of the puskesmas or hospital as well as information about the shortest path to the puskesmas or hospital. The size of the region and the volume of traffic present a challenge for people who are unfamiliar with the Karanganyar Regency's routes. The aim of this research is to enable the community to easily locate the health center and to provide access for numerous individuals who require assistance in locating the health center in Karanganyar Regency. Floyd-Warshall research methodology was used in this study to create this system while data collection from Karanganyar District Health Office is then required in this study. The results of this study are in the form of the closest route that is connected to Google Maps, which is information about the location of the health center in Karanganyar Regency which is beneficial for people outside Karanganyar Regency. This study's test findings, which used Floyd Warshall's results approach, further ensure its success in identifying the closest path. The test scenario and the available observations matched 91.6% of the 12 test components, according to the system functionality test. Based on the validity test, it has an average error in predicting the distance from the starting point to the search location of 98%.